Development Problem Based Learning Activities to Enhance Students Engagement in Class VII - Laksmi, Putu Satya Wadi; Nitiasih, Putu Kerti; Wahyuni, Luh Gede Eka (English Education Department STKIP Agama Hindu Singaraja, 2024)
This research addresses the critical issue of low student engagement in English language learning among seventh-grade students at SMPN 5 Singaraja, where preliminary observations revealed that only 3 out of 32 students actively participated in class discussions. The study aims to develop and implement Problem-Based Learning (PBL) activities to enhance cognitive, emotional, and behavioral engagement in English language learning. The research employs a mixed-methods developmental approach using the ADDE model (Analysis, Design, Development, and Evaluation). Data collection methods include classroom observations, structured interviews with teachers and students, questionnaires using both Guttman and Likert scales, document analysis of curriculum materials, and expert judgment evaluations. The study focuses on creating a prototype of PBL activities tailored to address the specific engagement challenges identified in the target classroom. Preliminary findings from the analysis phase indicate that 62.75% of students experience obstacles in cognitive engagement, 58.64% show low emotional engagement, and 34.29% demonstrate minimal behavioral participation. The research expects to demonstrate significant improvements in student engagement through the implementation of authentic, real-world problem-solving activities that encourage critical thinking and collaborative learning. The study's implications extend beyond the immediate classroom context, offering educational practitioners a framework for implementing PBL methodologies to enhance student engagement in English language learning, potentially transforming traditional passive learning environments into dynamic, participatory educational experiences.